Health Literacy: More Important Than Ever in the COVID-19 Pandemic (Turkey Health Literacy Journal, 2020)
At the time of writing this initial letter, I think we can all agree that we are living the strangest and one of the most disturbing times ever known. While on the eve of a new year, people hoped that 2021 would arrive healthier and issueless, no one could have predicted that in about 10 months societies around the world would experience these twists of life. In the midst of the COVID-19 pandemic, we see this health literacy special edition as an opportunity to highlight the importance of individual and community issues. At this special edition, we want to present national and international perspectives of special topic articles. Our aim is to increase the academic, strategic, bureaucratic and political awareness in order to make and implement practices for better understanding, caring and increasing health literacy. The COVID-19 pandemic has brought a huge burden and life change to countries, organizations and individuals. According to the report of the World Health Organization dated 10 December 2020, there are 68 165 877 known cases and, 1 557 385 deaths. Public health measures such as physical distance, avoiding crowded environments, remote work and education, quarantine, isolation are implemented in all countries to prevent the spread of COVID-19. Because of the fear, panic, mental health problems, economic problems, social problems, etc. pandemic has social effects in many areas. The negative effects of these on people’s mental health are obvious. With this mental state, it is very important that the society shows the correct health behavior for the control of the epidemic. The perception, acceptance and implementation of the interventions by the society is closely related to the health literacy level of the individuals. Limited and inadequate health literacy in society is actually a silent epidemic. Health literacy is a large and important issue in public health, but it is still globally underestimated, so it is considered a silent epidemic. It should not be ignored in the emergence of health problems, outbreaks and in making the right health behaviors, which are very important in the case of epidemics, and in the formation of community reactions. Health literacy is a social determinant of health, and although low levels of health literacy are associated with lack of education, poverty, unemployment and low socioeconomic status, those with higher education and income levels may also show low health literacy when faced with a new problem. Studies have shown that people with a high level of health literacy have a better perception of health knowledge. Also, higher health literacy is associated with a better health status, less health inequalities, and better health and well-being. The high level of health literacy increases the ability of individuals to make protective interventions by reducing fear and panic in the epidemic. Health literacy has been recognized as a critical factor in the evaluation of this health information, especially in today’s world where there is a lot of information and resources. The COVID-19 pandemic has suddenly revealed the inadequacy of the health literacy levels of the world’s population. In this sense, it is very important to strengthen the debate on this very health-related and important but overlooked issue. Improving Health Literacy has been shown to be an effective strategy in health promotion, disease prevention and control, and situations that currently require rapid interventions. Therefore, health literacy should be seen as an important element of social responsibility and resilience, and should be used as an important tool for both information buyers and providers to manage the current pandemic and the future. An interdisciplinary approach to improving health literacy is more important during this pandemic.